Hunger-induced convergence of personality traits towards ambush-predatory behavior in ball pythons (Python regius, Shaw 1802) - CRAIOVEANU, Octavian; SPATARO, Elisabeth; CRAIOVEANU, Cristina (Studia Universitatis Babeș-Bolyai Biologia, 2025)
Personality traits have been shown to be influenced by environmental and internal factors, hunger being one of the most important. The resulting behavior fluctuates greatly depending on the feeding ecology of the different species and intraspecific individual variation. In this study, we used eight captive-born juvenile ball pythons to examine the relationship between personality traits, namely shyness and exploratory tendencies, and the chronological postprandial-induced psychobiological effects on a seven-day interval that concluded with the installation of hunger. We found a strong correlation between shyness and hunger. Regarding exploratory predispositions, we found high individual variation at the beginning and middle of the postprandial cycle that evened out as hunger's influence started to be perceived. Notably, this study's outcomes have the potential to enhance our understanding of captive animal management techniques and contribute to improving zoo animal welfare. Article history: Received 13 January 2025; Revised 25 March 2025; Accepted 03 April 2025; Available online 25 June 2025